EasyHBM: Simple and Fast HBM Access for FPGAs Using High-Level-Synthesis - Schwenger, Lars; Holzinger, Philipp; Fey, Dietmar; Hernandez, Hector Gerardo Munoz; Reichenbach, Marc (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2022)
High-Level Synthesis (HLS) has become increasingly popular for FPGA accelerators. Its main benefit is the considerably simpler development and faster time-to-market than traditional RTL designs. HLS also allows developers with less in-depth hardware design knowledge to employ FPGA accelerators for their applications. However, like traditional CPUs, these designs often suffer from an insufficient memory bandwidth to provide data to all computational units. High-Bandwidth Memory (HBM) has been developed and recently added to commercial FPGAs to overcome the limited bandwidth. As stacked DRAM, it achieves a substantially higher bandwidth than traditional DRAM through its high number of independent memory channels. However, current HLS tools do not fully take this characteristic into account. They generate accelerators that either do not automatically use all available channels for HBM access and thus lose performance or require more complex manual data partitioning and replication schemes between the channels. That leads to failure to meet the expected gains of application developers. Therefore, in this paper, we propose an utterly application-independent way to efficiently handle HBM as a unified pool of memory in an HLS tool in a generic manner. It keeps the advantage of high bandwidth for many applications while hiding the multi-channel complexity from the developer’s HLS accelerator description. That enables the design of HLS cores that run efficiently on FPGAs without deep consideration of the available memory.
CRIS-Team Scopus Importer:2022-09-09

Implementation of 3D Automotive SAR Imaging - Noegel, Theresa; Reinecke, Marc; Schwenger, Lars; Heidbrink, Max; Hoffmann, Marcel; Vossiek, Martin (2024 21st European Radar Conference (EuRAD), 2024)
Autonomous vehicles demand a precise environmental understanding and are often reliant on radar technology for distance measurement and velocity evaluation. However, automotive radars suffer from poor angular resolution due to their limited aperture size. Synthetic Aperture Radar (SAR) mitigates this limitation by leveraging the vehicle’s movement to synthesize a larger aperture, which significantly enhances the angular resolution. While SAR has been utilized for 2D imaging in the automotive field, this work presents a novel approach to generate 3D SAR images by rotating a typical automotive radar sensor to obtain a real aperture in the elevation direction. By conventionally synthesizing the azimuth aperture through vehicle movement, a complete 3D SAR reconstruction of the environment becomes feasible. Real-world measurement results validate the theoretical expectations and demonstrate that additional height information can be provided. Based on these findings, we discuss the identified challenges, define measures to reduce the computational complexity, and derive a design proposal for a radar system suited for 3D automotive SAR application

Implementation of Real-Time Automotive SAR Imaging - Hoffmann, Marcel; Noegel, Theresa; Schüßler, Christian; Schwenger, Lars; Gulden, Peter; Fey, Dietmar; Vossiek, Martin (2023 20th European Radar Conference, 2023)
This paper presents measures to reduce the computation time of automotive synthetic aperture radar (SAR) imaging to achieve real-time capability. For this, the image formation, which is based on the Back-Projection algorithm, was thoroughly analyzed. Various optimizations were individually tested and analyzed on graphics processing units (GPU). Apart from the time reduction gained from these measures, the data size needed for processing was also drastically decreased. With a combination of all measures, a high-resolution SAR image of 30 m × 30 m that combines 8192 chirps can be reconstructed in less than 30 ms using a standard GPU. It is thus demonstrated that a real-time implementation of automotive SAR is possible.<br
Keywords: Power demand; Radar measurements; Graphics processing units; Radar imaging; Radar antennas; Real-time systems; Radar polarimetry; radar imaging; automotive radar; FMCW; SAR